Hydrogen extraction from methane-hydrogen mixtures from the natural gas grid by means of electrochemical hydrogen separation and compression - Mrusek, Stephan; Blasius, Marco; Morgenroth, Frank; Thiele, Simon; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
One interesting option to store and transport hydrogen in the future is to blend it into the natural gas grid. In this paper, we present technological insights regarding electrochemical hydrogen separation and compression (EHC/S), a technology that enables extraction of compressed and purified hydrogen from such blends. Our contribution discusses two use cases, namely i) hydrogen separation to recover purified hydrogen under pressure, and ii) hydrogen removal to protect downstream methane consumers from excessive hydrogen levels. Our experimental work with a laboratory scale EHC/S centers on efficiency aspects. We show that at low hydrogen contents in dry feed gas, gas humidification causes relevant thermal energy consumption, that cannot be provided by EHC/S waste heat. We also show that hydrogen recovery is restricted by mass transport if the residence time in the EHC device is too short. Simultaneous hydrogen separation and compression from 5% hydrogen in methane is demonstrated yielding hydrogen at 6 bara at the cathode.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Electrochemical hydrogen compression; Electrochemical hydrogen separation; Hydrogen purification; Hydrogen storage; Natural gas grid